Exploring the Effects of Sleep Deprivation on Physical Performance: An EEG Study in the Context of High-Intensity Endurance - Shanguang Zhao; Majed M. Alhumaid; Hai Li; Xin Wei; Steve SHYH-Ching Chen; Hongke Jiang; Yuwu Gong; Yun Gu; Haiquan Qin (Sports Medicine - Open)
Abstract Background While the effects of sleep deprivation on cognitive function are well-documented, its impact on high-intensity endurance performance and underlying neural mechanisms remains underexplored, especially in the context of search and rescue operations where both physical and mental performance are essential. This study examines the neurophysiological basis of sleep deprivation on high-intensity endurance using electroencephalography (EEG). In this crossover study, twenty firefighters were subjected to both sleep deprivation (SD) and normal sleep conditions, with each participant performing endurance treadmill exercise the following morning after each condition. EEG signals were recorded before and after high-intensity endurance exercise, and power spectrum analysis and functional connectivity analysis were performed on sleep related frequency bands rhythm: δ (0.5–4 Hz) and θ (4–8 Hz). The EEG power spectral and functional connectivity were measured by repeated measure analysis of variance. Results The SD condition had an average sleep duration of 3.78 ± 0.69 h, while the duration for normal sleep was 7.63 ± 0.52 h. After high-intensity endurance exercise, the SD condition had a higher maximum heart rate (p < 0.05) and shorter exercise time (p < 0.05) than normal sleep. Compared with before exercise, the δ band in the left parietal lobe P7 channel increased significantly (p < 0.01), and the θ band in the central Cz channel and the left and right parietal lobe P7 and P8 channel increased significantly (p < 0.01 & p < 0 0.05) in SD and normal sleep conditions after exercise. After exercise, compared with normal sleep, the δ band power in occipital O1 and Oz channels and parietal P7 and TP7 channels in SD significantly decreased (p < 0.05 & p < 0.01); the power of the θ band decreased significantly in the occipital O1 channel, central CZ channel and the left and right parietal P7 and P8 channel (p < 0.05 & p < 0.01). Whole connectivity showed a significant increase (p = 0.001) in the δ band for the SD condition at post-exhaustion. Local connectivity analysis identified a localized network in the δ band with reduced (p < 0.001) post-exhaustion in the SD condition displaying inter-hemispheric differences in certain connections (FP1-CP4, T7-C4, T7-TP8, and O1-FT8) and intra-hemispheric (C3-CPz and Pz-P4) variations. Conclusions Sleep deprivation significantly reduced maximum endurance performance, indicating decreased neural activity in the central and parietal brain regions. Alterations in δ and θ frequency band power, along with disrupted connectivity, may highlight the neurophysiological basis underlying this decline.